Zastosowanie systemu ARAMIS do pomiarów odkształceń konstrukcji murowych = Application of ARAMIS system for measurement of deformations of masonry - Urbańska, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of measurements of displacements and strains obtained on fragments of walls made of bricks. In addition to the Instron measurements, the displacements were measured on the specimen surface by using the modern non-contact measuring system ARAMIS, which has a direct interface with the strength testing machine and determines displacements by means of two cameras. The results were used to determine the average strain and the observation of the propagation of cracs in masonry panel.
Keywords: system Aramis; odkształcalność muru; zarysowania; propagacja zarysowań; deformability of the masonry; cracks; propagation of cracks